Postpartum atypical haemolytic uremic syndrome: a rare clinical entity - Sablok, Aanchal; Gupta, Taru; Gupta, Sangeeta; Duggal, R. K.; Tiwari, Amrita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
P-aHUS has incidence of 1 in 25000 pregnancies. It’s characterized by microangiopathic haemolytic anemia, thrombocytopenia and renal failure. Mrs X, 26 year old lady, G2 P1L1 with 39 weeks POG came to emergency of a tertiary care hospital. She underwent LSCS in view of previous caesarean section not willing for trial of labour. Antenatal, intrapartum and immediate post operative period were uneventful. However, she became anuric 36 hours post operatively. Laboratory investigations suggested hemolysis. Complement system evaluation showed decreased complement levels. Diagnosis of p-aHUS was made by taking multidisciplinary approach and renal biopsy. Patient received 4 sessions of plasmapheresis and symptomatic treatment. Gradually her urine output increased and she was discharged with the baby on post operative day 19. Diagnosis of p-aHUS is tricky owing to similar clinical features with many other pregnancy associated conditions. Timely management and diagnosis are imperative to save the mother’s life.